Dampak Merokok terhadap Kesehatan Lingkungan: Sebuah Tinjauan Naratif - Kemal Akbar Suryoadji; Reynardi Larope Sutanto; Christopher Christian; Elza Nur Warsa Putra; Muhammad Faruqi; Kevin Tadeus Simanjuntak; Ilham Qurrota A’yun; Najma Ali (PT Kalbe Farma Tbk., 2024)
Introduction: Smoking, which involves tobacco as the primary material, has extensive impacts on environmental and human health. This study incorporates literature and research related to the environmental impacts of smoking. Methods: This research uses the literature review method, referencing relevant sources. Document searches were conducted through Google Scholar and manual searching using the keywords “(Smoking) AND (Environmental Health).” Results: The environmental impacts of smoking are highly complex, including air pollution, littering from cigarette butts, and the effects of tobacco processing and production on land and water. Regulatory issues pose challenges in controlling the negative environmental impacts of smoking. Discussion: Air pollution resulting from smoking includes a significant increase in carbon dioxide emissions and a substantial contribution to climate change. Littering cigarette butts leads to the accumulation of harmful plastic waste in marine ecosystems and human health. Tobacco production also carries serious consequences, including deforestation, agrochemical use, and pollution. Controlling tobacco and cigarette use requires comprehensive measures, including cost regulation, advertising bans, and strict monitoring. Stronger regulations and collaborative efforts are needed to address the environmental impacts of smoking effectively. Conclusion: Smoking has significant impacts on environmental health, including air pollution, littering pollution, and the effects of tobacco production. Further efforts are necessary to control these negative impacts through effective regulations and raising public awareness of the environmental consequences of smoking.